2022
DOI: 10.1109/access.2022.3226247
|View full text |Cite
|
Sign up to set email alerts
|

3D-FOX—A 3D Transient Electromagnetic Code for Eddy Currents Computation in Superconducting Magnet Structures: DTT TF Fast Current Discharge Analysis

Abstract: Bulky metallic structures are needed in the toroidal field (TF) superconducting magnets for fusion applications to withstand the large Lorentz forces acting on the winding. The pulsed coil operation during a plasma scenario and the fast current discharge, or a plasma disruption event in off-normal operating conditions, cause transient magnetic fields, inducing eddy currents in the TF structures. The eddy currents generate heat in the structures heating in turn the winding pack, eroding the temperature margin: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The EM model for the evaluation of the eddy currents induced in the coil casing during the FD is developed within the 3D-FOX, a finite element electromagnetic code developed at Politecnico di Torino [8]. The model solves Faraday's and Ampère's laws using the A-formulation.…”
Section: Electromagnetic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The EM model for the evaluation of the eddy currents induced in the coil casing during the FD is developed within the 3D-FOX, a finite element electromagnetic code developed at Politecnico di Torino [8]. The model solves Faraday's and Ampère's laws using the A-formulation.…”
Section: Electromagnetic Modelmentioning
confidence: 99%
“…The eddy currents' distribution is then used to evaluate the power distribution in the TF coil casing by means of Ohm's law. The Joule power deposition is suitably averaged before providing it as input to the TH model, as explained in [8].…”
Section: Electromagnetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The FD consists in the controlled discharge of the 18 TF coil current with a linear ramp lasting 7.5 s [23]. This coil current variation, causing magnetic field variations, induces again AC losses (computed according to the two cases listed above for the PD) and eddy currents, computed with the model presented in [24]. The power deposition is different in each of the 16 poloidal cuts, but here it is assumed uniform within each of them.…”
Section: B Plasma Disruption and Fast Current Dischargementioning
confidence: 99%
“…The power deposition is different in each of the 16 poloidal cuts, but here it is assumed uniform within each of them. Note that in [24] it is shown that a linear FD induces The entire heat load evolution is reported in Fig. 6(b), and the values of energy deposited are collected in Table I.…”
Section: B Plasma Disruption and Fast Current Dischargementioning
confidence: 99%